Prototype Robot Pemadam Api Otomatis Berbasis Arduino dengan Sensor Api dan Kamera - Dermawan, Tengku Mhd Aidil; Roza, Indra; Siregar, Lisa Adriana (Universitas Harapan Medan, 2025)
Fire is one of the events that can cause major impacts, ranging from material losses to life safety risks. To overcome this, technology is needed that can detect and extinguish fires quickly, especially in areas that are difficult to reach or too dangerous for humans. This study aims to design and develop a prototype of an Arduino-based automatic fire extinguishing robot equipped with a fire sensor and camera. The fire sensor is used to detect the presence of a fire source, while the camera functions as a visual support tool that helps the robot navigate and identify the position of the fire more accurately. This robot is designed to be able to move independently to the fire point after successful detection. Once close enough, the robot will activate the extinguishing mechanism to put out the fire. This prototype was tested in various environmental scenarios and varying fire intensities to measure the level of detection accuracy, response speed, and effectiveness in the extinguishing process. The test results show that the robot is able to detect and extinguish small-scale fires with a high success rate. Although there are still some limitations in terms of speed and detection distance, this prototype shows great potential as a supporting technology for fire extinguishing, especially for high-risk areas. With further development, it is hoped that this robot can function as a supporting device in handling small-scale fires and as a solution to maintain human safety from direct exposure to fire risks.